Physical Activity and Its Correlates among Adults in Malaysia: A Cross-Sectional Descriptive Study. - Tam Cai Lian; Gregory Bonn; Yeoh Si Han; Yap Chin Choo; Wong Chee Piau (PLoS ONE, 2016)
Obesity and rates of non-communicable diseases linked to physical inactivity have increased dramatically in Malaysia over the past 20 years. Malaysia has also been identified as one of the least physically active countries in the world with over 60% of adults being essentially sedentary. This study examines the relationship of socio-demographic factors to physical activity among 770 adults from 3 Malaysian states. Physical activity levels were significantly related to ethnicity, gender, age, occupation and educational level. Controlling for inter-relationships among these variables; age, gender, Chinese ethnicity and education level were found to have unique effects on total physical activity, as well as moderate and vigorous exercise. As would be expected, younger people were more physically active, engaging more in both moderate and vigorous types of exercise and males were generally more active than females. Contrary to findings from many developed countries, however, more educated Malaysians were less likely to engage in all types of physical activity. Ethnic Chinese participants, and to a lesser degree Indians also consistently reported lower levels of activity. Possible intervention strategies are discussed that specifically target ethnic and cultural norms related to physical activity. Future research programs exploring barriers to participation and perceptions of physical activity, as well as programs to encourage active life styles among youths are also suggested.